Body measurements of etawa crossbreed goats in Sidamulih District, Pangandaran Regency - Fajar rahman syawali; Didin Supriat Tasripin; Bambang Kholiq Mutaqin (Fakultas Pertanian Universitas Majalengka, 2025)
Goats are small ruminants useful for humans as animal protein producers in the form of milk and meat. This research was carried out on 25-26 May 2024 in Sidamulih District, Pangandaran Regency. This research aimed to determine the measurements of etawa crossbreed goats, measuring 33 goats with ages <1 year, 1-2 years, and >2 years in the Sidamulih District. The research method used is a quantitative descriptive method. The results showed that the body measurements of etawa crossbreed goats in Sidamulih District are relatively uniform; however, in Doethe, the doe <1 year old is not uniform. The average chest circumference in Doedoe and bucks aged <1 year, 1-2 years, >2 years were 53.10±13.90 cm, 72.92±10.92 cm, 78.55±12.75 cm, and 51.90±0.60 cm, 82.83±6.83 cm, 90.20±14.20 cm, respectively. The average body lengths of Doedoe and bucks aged <1 year, 1-2 years, >2 years were 53.10±13.90 cm, 72.92±10.92 cm, 78.55±12.75 cm, and 51. 90±0.60 cm, 76.83±5.83 cm, 81.80± 12.20 cm, respectively. The average shoulder height of Doedoe and bucks aged <1 year, 1-2 years, >2 years were 51.37±10.37 cm, 73.88±10.88 cm, 77.30±7.89 cm, and 50.25±1.75 cm, 78.05±1.95 cm, 86.00±9.70 cm, respectively. The last variable, the average body weights of Doe and bucks aged <1 year, 1-2 years, >2 years were 17.50±9.50 kg, 42.13±4.88 kg, 53.00±4.00 kg, and 14.50±0,50 kg, 43.20±11.80 kg, 68.40±27.40 kg. These results indicate that female and male goats aged 1-2 years and >2 years have met the SNI requirements. Female goats aged <1 year do not meet the SNI requirements, while male goats aged <1 year and >2 years do not meet the SNI requirements.